Struktur Modal, Ukuran Perusahaan, Dan Earnings Response Coefficient: Profitabilitas Sebagai Variabel Mediasi - Anggi Tadani (Jurnal Literasi Akuntansi, 2022)
Purpose: This study aims to examine whether capital structure and firm size can affect the earnings response coefficient and is mediated by profitability. Method: The sample uses manufacturing sector companies listed on the Indonesia Stock Exchange for the last 6 years. Sample selection using pruprosive sampling technique in order to obtain 10 companies. Testing the sample using multiple linear regression analysis and path analysis to test the mediating variable using the SPSS 20 analysis tool. Finding: The results prove that capital structure has a positive effect on profitability, firm size has a positive effect on profitability, capital structure has a negative effect on the earnings response coefficient (ERC), firm size has a positive effect on the earnings response coefficient (ERC), profitability has a positive effect on the earnings response coefficient ( ERC), Profitability mediates the effect of capital structure on earnings response coefficient (ERC), Profitability mediates the relationship between firm size and earnings response coefficient (ERC). Novelty: This research has something that has not been done before, and there are comparisons with studies that have been done previously.